Answer:
a.51
b.131.5
d.131.5
w.131.5
x.51
y.131,5
z.51
don't know the rest
Step-by-step explanation:
The equations a = n, b = 2n + 6 and c = n² - 1 are polynomials, and the expression for ab - c is n² + 6n + 1
<h3>How to determine the expression for ab - c?</h3>
The polynomials are given as:
a = n
b = 2n + 6
c = n² - 1
The expression ab - c is calculated using:
ab - c = n * (2n + 6) - (n² - 1)
Expand
ab - c = 2n² + 6n - n² + 1
Collect like terms
ab - c = 2n² - n² + 6n + 1
Evaluate
ab - c = n² + 6n + 1
Hence, the expression for ab - c is n² + 6n + 1
Read more about polynomials at:
brainly.com/question/4142886
#SPJ4
A+S=589
S=a-61
A+A-61=589
2a=589+61
2a=650
A=325
S=325-61
S=264
Hope this helps
Answer:
gdjtdigdigxigxig
Step-by-step explanation:
hzhfsitdutxigxiycoyxigxitxi
Karen = x
bill = 2x - 9
total = x + 2x - 9 = 3x - 9